GERAKAN MADI DI SALENA - Nofian, (Manaqib: Jurnal Sejarah Peradaban Islam dan Humaniora, 2022)
This article attempts to answer the following 3 questions: 1) what is the background of the Madi Movement in Salena?; 2) How was the development process of the Madi Movement?; 3) How did the Madi Movement end? The research questions were solved using a historical methodology through a sociological and anthropological approach with analysis tools of Movement theory supported by several religious movement concepts. Source searches were carried out at government offices, regional libraries, Tadulako University libraries, and were completed with observations and interviews. The results of this study found three things, namely; First, the emergence of the movement in Salena as a form of social protest for remote communities as a result of social changes that occurred in Palu City. The second development of the movement in Salena was led by Madi as a shaman (sando) and also as a silat teacher (kantau) who founded a college called "Dente Sepuluh". Third, the peak of the movement in Salena stems from a clash between the police and Madi's group that killed three police officers. Madi's death and the detention of a number of his groups marked the end of the Salena Movement.